USING FACEBOOK TO PROMOTE STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH - Hustarna, Hustarna - (Universitas Muria Kudus, 2023)
Learning English as a foreign language in Indonesia is not easy for many students, not only junior and senior high school students but also college/university students. It often makes them unable to be active in the teaching and learning process and have low motivation and false attitudes toward learning English. As a result, they would get low achievement in English. Considering the case, teachers need to think of ways to make students enjoy learning English both inside and outside the classroom. This study aims at elaborating on Facebook as one of the online social media that can be used to attract students’ active engagement in English teaching and learning process. This study employed a literature research methodology (Lin, 2009; vom Brocke et al., 2009) by using qualitative analysis. The findings showed that Facebook, which most people, especially in Indonesia, usually use it only for fun, can also be used as a medium to get students involved in the teaching and learning process. By using Facebook, students are able to participate in learning English whenever and wherever they are. Besides, teachers can monitor, facilitate, and evaluate students' participation by commenting on the student's responses in unlimited space and time. Based on some research findings, Facebook can be used to enhance learning. Finally, Facebook has many benefits for students if it is used and managed well.